2022
DOI: 10.1039/d1qo01349a
|View full text |Cite
|
Sign up to set email alerts
|

1D alignment of proteins and other nanoparticles by using reversible covalent bonds on cyclic peptide nanotubes

Abstract: Self-assembling cyclic peptide nanotubes are supramolecular structures whose diameter and external surface properties are precisely controlled. In this communication we describe a general strategy to align different molecules on top...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…[24] Another noteworthy advantage of cyclic peptides with alternative chirality is that the exposed surface could provide appropriate amino acid side chains for further modifications by incorporating natural or unnatural amino acids with functional groups. [25] The nanotubular structures in which all the side chains project perpendicularly toward the tube axis to provide ample spaces for conjugating with polymers or peptides. The report showed that cyclic d/l peptides could display superior solubility in water or lipophilicity to interact with biological membranes by tuning the hydrophilicity and hydrophobicity through side chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Another noteworthy advantage of cyclic peptides with alternative chirality is that the exposed surface could provide appropriate amino acid side chains for further modifications by incorporating natural or unnatural amino acids with functional groups. [25] The nanotubular structures in which all the side chains project perpendicularly toward the tube axis to provide ample spaces for conjugating with polymers or peptides. The report showed that cyclic d/l peptides could display superior solubility in water or lipophilicity to interact with biological membranes by tuning the hydrophilicity and hydrophobicity through side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Another noteworthy advantage of cyclic peptides with alternative chirality is that the exposed surface could provide appropriate amino acid side chains for further modifications by incorporating natural or unnatural amino acids with functional groups [25] . The nanotubular structures in which all the side chains project perpendicularly toward the tube axis to provide ample spaces for conjugating with polymers or peptides.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the reported work of cyclic peptides produced via an irreversible amide coupling reaction, featuring a symmetrical backbone [16] self‐assemble to form 1D nanotubular structures and even 2D nanosheets [17] (Figure1a). Studies mainly focus on the modifications of nanotubes via a reversible covalent linkage through peptide side chains [9b,e,18] . However, the self‐assembly (SA) behaviors and the conformational tuning diversity of cyclic peptides with an asymmetrical backbone, such as incorporating a heterocycle has been less explored.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41] The highly ordered supramolecular structures have been employed as scaffolds to enable the precise arrangement of functional moieties, including drugs, π-conjugated chromophores, proteins, and nanoparticles. [42][43][44][45][46][47][48] More importantly, the densely packed polymer chains surrounding the cyclic peptide cores are expected to create a confined microenvironment. Therefore, we envisaged that by positioning the cyanine moieties near the core area within the supramolecular polymeric nanotubes, while molecularly dispensing them along the tubular structures, the undesired cis-trans photoisomerization and ACQ could be inhibited simultaneously, thus greatly boosting the fluorescence quantum yields of cyanine dyes.…”
Section: Introductionmentioning
confidence: 99%